PERANCANGAN SISTEM KENDALI VOLUME PENGISIAN AIR ISI ULANG GALON DENGAN SENSOR ALIRAN AIR BERBASIS OUTSEAL PLC - Huda, Miftakhul; Arfan Haqiqi Sulasmoro (Universitas Muhammadiyah Surabaya, 2024)
Drinking water is needed by humans. Most people in Indonesia still use well water as a source of clean water to fulfil their daily needs. With the increase in activity and the development of the times, some people switch to using refill drinking water for their daily drinking needs. The process at drinking water refill depots is generally still carried out using relatively modern equipment, but the process of filling water into gallons is still manual. The operator must press a button to start filling and pay attention to the level of water fullness during the filling process. This is inefficient and can also lead to uncertainty of the volume of water filled in gallons. Automatically, consumers can be disadvantaged because the volume of water entering the gallon is not the same even with the same operator. this certainly has obstacles. So it is proposed to make a system that is able to regulate the volume of water that has been determined. The methodology used with the stages of design and manufacture, testing, data analysis, evaluation of research results and preparation of research reports. The system is made by utilising Outseal PLC as a controller, the volume of water is obtained from the pulse calculation given by the water flow sensor, while the HMI is used as an interface in using the system connected to Outseal PLC via Bluetooth. The test results for 1 litre of water with Wasser Pump PB-60EA average pulse sent as many as 350 pulses and a length of time of 13 seconds while the test results with pump 775 12VDC average pulse sent as many as 307 pulses and a length of time of 20 seconds.